Enhancing Tomato (Solanum lycopersicum L.) Resistance Against Bacterial Canker Disease (Clavibacter michiganensis ssp. michiganensis) via Seed Priming with β-Aminobutyric Acid (BABA) - Nazlı Özkurt; Harun Bektas; Yasemin Bektas (Horticulturae)
Many stressors contribute to productivity and quality losses in agricultural production, ranging from the rising global population to shrinking agricultural lands. To boost yield and quality, plants must be protected from abiotic and biotic stressors. Seed priming is the process of boosting germination and seedling development by treating seeds with particular pre-treatments before germination. Seed priming is used to improve plant yield and germination. Plant defense elicitors stimulate the plant’s natural immune system when administered externally, strengthening the plant and making it more resistant/tolerant to diseases. β-Aminobutyric Acid (BABA) is a plant defense elicitor, and in this study, the effect of BABA seed priming on Clavibacter michiganensis ssp. michiganensis (Cmm), which causes bacterial cancer in tomato (Solanum lycopersicum L.), was investigated. Tomato seeds were subjected to seed priming for 72 h with 12 mM BABA (BABA priming) or water (water priming) as the control group. Tomato seedlings that germinated normally were utilized as a positive control. When the plants reached the 3–4 leaf stage, they were infected with Cmm. According to the data, BABA priming was the most effective experimental group in reducing disease severity. Furthermore, it has been shown that the use of BABA as a spray or water-priming application gives better protection than the control treatment. To understand the molecular basis of this suppression, plant samples were obtained at two separate time points (0th and the 7th day), and transcriptional changes of essential plant immunity genes (NPR1, PAL, PR1, WRKY70, WRKY33b, TPK1b, and PR5) were studied. The qRT-PCR results showed that NPR1 gene expression increased considerably with the BABA priming treatment compared to the control. BABA priming at the 0th hour enhanced NPR1 gene expression by approximately five times. In addition, BABA priming increased PR1 gene expression. Furthermore, foliar spraying of BABA (BABA priming+BABA-Sp) on seed-primed plants resulted in a nine-fold increase in PR1 gene expression. At day 7, the BABA priming+Cmm treatment increased PR5 gene expression. Along with the control of other genes, the molecular architecture of BABA seed priming has been attempted to be discovered. The application of BABA seed priming is expected to contribute to the literature and have favorable impacts on plant protection against Cmm.